Evidence-Based Periodontal and Peri-Implant Plastic Surgery A Clinical Roadmap from Function to Aesthetics - Chambrone, Leandro.; Chambrone, Leandro. (Springer International Publishing : Imprint: Springer, 2015)
This atlas, featuring numerous superb illustrations and vivid photographs, aims to create a bridge between research and practice in the field of periodontal plastic surgery and cosmetic dentistry with a view to enabling optimal decision making in daily practice. After an opening overview of evidence-based decision making and discussion of treatment planning, subsequent chapters address the surgical treatment of recession-type defects, use of soft tissue substitutes, aesthetic clinical crown lengthening, and peri-implant plastic surgery. Illustrated case studies depict application of the described surgical procedures in daily practice, and advice is provided on clinical indications and contraindications and basics of the surgical sequence. In addition, critical summaries of the results of systematic reviews are provided. Further chapters consider aspects of multidisciplinary decision-making and present decision trees for soft tissue augmentation procedures proposed by the American Academy of Periodontology. The atlas will be a valuable clinical guide for general dentists and specialists in periodontology/periodontics and implantology.